Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.06.03.21258263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards antibiotic use and resistance among the veterinarians in Bangladesh

Abstract: Background The emergence of antimicrobial resistance (AMR) is growing public health concern around the world. When a number of studies have emphasized the Knowledge, Attitude and Practice (KAP) regarding antibiotic use and resistance in humans, little attention has been paid to the veterinary sector. The aim of this study was to understand the KAP towards antibiotic use and resistance among the veterinarians in Bangladesh. Methods A cross-sectional online based questionnaire survey was conducted from August to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Numerous studies conducted in various countries have consistently shown that veterinarians have good KAP related to AMU and AMR, which agreed with the previous study ( 23 26 ). Specifically, 86.5% mentioned that they did not use antimicrobials as growth promoters, which was comparable to the finding of Bangladesh (80.0%) ( 18 ). Approximately 89.0% of the veterinarians agreed that vaccination could reduce the use of antimicrobials in poultry, and 75.6% believed that using narrow-spectrum antimicrobials are a better choice than broad-spectrum, which is similar with a study conducted in Bhutan ( 27 ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Numerous studies conducted in various countries have consistently shown that veterinarians have good KAP related to AMU and AMR, which agreed with the previous study ( 23 26 ). Specifically, 86.5% mentioned that they did not use antimicrobials as growth promoters, which was comparable to the finding of Bangladesh (80.0%) ( 18 ). Approximately 89.0% of the veterinarians agreed that vaccination could reduce the use of antimicrobials in poultry, and 75.6% believed that using narrow-spectrum antimicrobials are a better choice than broad-spectrum, which is similar with a study conducted in Bhutan ( 27 ).…”
Section: Discussionsupporting
confidence: 64%
“…Only 15.0% of veterinarians were female, which was lower than the overall ratio of female veterinarians among registered veterinarians (22.9%) in Nepal ( 14 ). However, a previous study in Bangladesh also reported a similar proportion (14.9%) of female veterinarian engaged in practice ( 18 ). This gender distribution discrepancy may be due to the employment of female veterinarians in administrative and academic roles rather than in poultry practices.…”
Section: Discussionmentioning
confidence: 72%
“…Regarding specific observations, this study noted that the average mortality rate among broiler poultry flocks was 9.3 ± 15.5%, slightly lower than in previous studies [21]. Additionally, this study found that the average income per 100 birds was USD 43.8 ± 22.6, with a range from USD 0 to 105.7.…”
Section: Discussioncontrasting
confidence: 43%
“…This difference could be due to older farmers being more self-reliant and having greater exposure to training and work experience than their younger counterparts. A previous study on KAP in Bangladesh also highlighted the influence of farmers' age and experience on AMU and AMR in poultry production [21]. Approximately 9.2% of farmers reported not using antimicrobials throughout the entire broiler production cycle, while 90.8% used antimicrobials at least once during the production cycle, indicating the continued prevalence of AMU in broiler production.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation